2017
DOI: 10.1080/14737159.2018.1419065
|View full text |Cite
|
Sign up to set email alerts
|

Point-of-care diagnostics for respiratory viral infections

Abstract: Successful treatment outcomes for viral respiratory tract infections presenting from primary health care to quaternary hospitals will only be achieved with rapid, sensitive and specific identification of pathogens to allow effective pathogen-specific antiviral therapy and infection control measures. Areas covered: This review aims to explore the different point-of-care tests currently available to diagnose viral respiratory tract infections, discuss the advantages and limitations of point-of-care testing, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
73
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(78 citation statements)
references
References 81 publications
(94 reference statements)
0
73
0
5
Order By: Relevance
“…Although RT‐PCR was used to detect viruses in 17 included studies, these tests have not shown a consistent level of accuracy in detecting viral pathogens. Basile et al 63 reviewed point‐of‐care diagnostic tests including RT‐PCR for respiratory infections and found that sensitivity for viral pathogens varied from 20%–94% depending on the type of test, the individual viruses analyzed, the manufacturer, and the specific technique used. Zhang et al 64 combined serology (antibody testing) with RT‐PCR to analyze the additive diagnostic yield with a combined testing approach.…”
Section: Discussionmentioning
confidence: 99%
“…Although RT‐PCR was used to detect viruses in 17 included studies, these tests have not shown a consistent level of accuracy in detecting viral pathogens. Basile et al 63 reviewed point‐of‐care diagnostic tests including RT‐PCR for respiratory infections and found that sensitivity for viral pathogens varied from 20%–94% depending on the type of test, the individual viruses analyzed, the manufacturer, and the specific technique used. Zhang et al 64 combined serology (antibody testing) with RT‐PCR to analyze the additive diagnostic yield with a combined testing approach.…”
Section: Discussionmentioning
confidence: 99%
“…A positive result in an asymptomatic patient should be cautiously interpreted because it may reflect residual shedding or viral persistence. 19 The exact role of respiratory viruses in higher-risk BRUE therefore remains unclear. As we continue to develop our understanding of patients with a higher-risk BRUE, our findings align with the tiered pathway for the evaluation of a higher-risk BRUE, in which a rapid viral respiratory panel is included in the initial evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…Any ideal POCT should fulfill the ASSURED criteria of the World Health Organization to be applicable in resource-limited settings (Mabey et al, 2004). Currently, this is most likely true for tests based on lateral flow immunochromatography but coming improvements e.g., in miniaturization and battery capacity may facilitate the use of other test principles (Basile et al, 2018).…”
Section: Priorities For the Development Of New Poctsmentioning
confidence: 99%
“…In contrast to lab-based tests, point-of-care tests (POCTs) are performed at the site of sample collection (e.g., bedside, physician's office, or emergency department) and provide results usually in <2 h (Basile et al, 2018;Vos et al, 2019). Furthermore, they require only little hands-on time and no specific laboratory training as most critical steps are automated in a single device.…”
Section: Introductionmentioning
confidence: 99%